Pubertal gynecomastia incidence among 530,000 boys: a cross sectional population based study - Berger, Ori; Hornik-Lurie, Tzipi; Talisman, Ran (Frontiers in Pediatrics, 2024)
Background: Adolescent gynecomastia, a benign proliferation of male breast tissue, can lead to psychological issues during adolescence. The prevalence varies widely (4%-69%). The incidence peaks are during neonatal, pubertal, and senescent periods. Its affect on emotional well-being necessitates understanding and occasional intervention. This study aimed to determine the incidence of gynecomastia among male adolescents aged 12-15 years.: A retrospective cross-sectional study utilized the Clalit Health Care Services database (2008-2021) with a population of approximately 4.5 million. Participants aged 12-15 years were included if diagnosed with gynecomastia (International classification of diseases-9 code 611.1) and having a body mass index (BMI) measurement and no obesity diagnosis (ICD9 code 278.0). Data analysis included incidence rates and associations with ethnicity, age, BMI, and socioeconomic status.Results: 531,686 participants included with an incidence of 1.08%. Of all participants, 478,140 had a BMI≤25 with an incidence of 0.7%, and 0.25%-0.35% yearly, and 70% of gynecomastia patients were aged 13-14 years. The prevalence of gynecomastia differed between Jews (1.28%) and Arabs (0.67%), but the disparity diminished when socioeconomic status was considered.Conclusions: This unprecedented Population study establishes a definitive rate of true pubertal gynecomastia, revealing a lower yearly incidence as compared to previous reports. The higher observed prevalence among Jewish adolescents, may be caused due to complex interactions between different influencing factors. Understanding these dynamics can aid in formulating more targeted interventions and policy strategies to address gynecomastia's affect on adolescent well-being.